Diagnostics Accuracy of Magnetic Resonance Imaging in Detection of Atherosclerotic Plaque Characteristics in Carotid Arteries Compared to Histology: A Systematic Review - Pakizer, David; Kozel, Jiří; Elmers, Jolanda; Feber, Janusz; Michel, Patrik; Školoudík, David; Sirimarco, Gaia (Journal of magnetic resonance imaging, 2025)
Carotid plaque composition represents one of the main risk factors of future ischemic stroke. MRI provides excellent soft tissue contrast that can distinguish plaque characteristics. Our objective was to analyze the diagnostic accuracy of MRI imaging in the detection of carotid plaque characteristics compared to histology in patients with symptomatic and asymptomatic carotid atherosclerosis through a systematic review. After prospective registration in PROSPERO (ID CRD42022329690), Medline Ovid, Embase.com, Cochrane Library, and Web of Science Core were searched without any search limitation up to May 27, 2022 to identify eligible articles. Of the 8168 studies, 53 (37 × 1.5 T MRI, 17 × 3 T MRI) evaluated MRI accuracy in the detection of 13 specific carotid plaque characteristics in 169 comparisons. MRI demonstrated high diagnostic accuracy for detection of calcification (3 T MRI: mean sensitivity 92%/mean specificity 90%; 1.5 T MRI: mean sensitivity 81%/mean specificity 91%), fibrous cap (1.5 T: 89%/87%), unstable plaque (1.5 T: 89%/87%), intraplaque hemorrhage (1.5 T: 86%/88%), and lipid-rich necrotic core (1.5 T: 89%/79%). MRI also proved to have a high level of tissue discrimination for the carotid plaque characteristics investigated, allowing potentially for a better risk assessment and follow-up of patients who may benefit from more aggressive treatments. These results emphasize the role of MRI as the first-line imaging modality for comprehensive assessment of carotid plaque morphology, particularly for unstable plaque. EVIDENCE LEVEL: 2 TECHNICAL EFFICACY: Stage 2.
Keywords: diagnostic accuracy; Male; nemoci arterie carotis; magnetická rezonanční tomografie; Carotid Artery Diseases; mužské pohlaví; Carotid Arteries; reprodukovatelnost výsledků; lipid‐rich necrotic core; Reproducibility of Results; carotid stenosis; arteriae carotides; lidé; ženské pohlaví; Humans; Sensitivity and Specificity; senzitivita a specificita; carotid plaque; Magnetic Resonance Imaging; aterosklerotický plát; Female; atherosclerosis; intraplaque hemorrhage; Plaque, Atherosclerotic